Polypropylene foams under CO2 batch conditions: From formulation and rheological modeling to cell-growth simulation. (18th March 2021) - Rainglet, Benoît; Chalamet, Yvan; Bounor-Legaré, Véronique; Delage, Karim; Forest, Charlène; Cassagnau, Philippe
Abstract: The objective of this work was to study the development of polypropylene (PP) foams with low density (<100 kg m −3 ) using a CO2 batch process. To carry out this study, we used a PP-g-MA that was chemically modified by reactive extrusion to obtain polymer branched structures. Two reagent systems were selected on the basis of chemical reactions with maleic anhydride—the first one is based on the reaction between maleic anhydride and primary amines (MA/NH2, triamine, Jeffamine T-403), and the second one is based on ionic interactions from Zn neutralization. Both of these systems have shown that it is possible to obtain branched PP structures favorable to CO2 foaming and were compared to a commercial, high-melt-strength PP. We have shown that the branched structure of polymer chains can be defined on the basis of a rheological criterion. It defines the notion of fractal behavior (coupling of relaxation modes), which polymer chains must have for nonlinear behavior (strain hardening). This criterion has been defined by analogy with the sol-gel transition, tan δ = 1. Finally, in terms of modeling and simulation, the plasticizing effect of CO2 was modeled from the experimental rheological behavior of the PP plasticized with synthetic oil. A theoretical power law was derived and was then introduced in the mass balance equations to predict the cell growth during depressurization. Graphical abstract: Image 1 Highlights: Branched polypropylene chains are synthesized from chemical modification of PP-g-MA by reactive extrusion. The branched chain structures are designed on the basis of a linear rheological criterion: tan δ = 1 (sol-gel transition). The extensional transient viscosity is successfully predicted from the K-BKZ model. PP foams of low density (ρ < 100 kg m −3 ) are developed under CO2 batch foaming conditions. The growth of a foam cell is successfully simulated from nonlinear rheological behavior.